Indonesia-India Bilateral Relations Under Jokowi & Modi Leaderships: An Indonesian Perspective - Mohd Agoes Aufiya (International Journal of Qualitative Research, 2022)
This article analyses and assess Indonesia-India relations under the administration of President Joko Widodo and Prime Minister Narendra Modi during the first term as well as at the beginning of the second term from 2014-2021. The analysis is divided into the key aspects, the leadership background including political carrier, political party and their respective vision or foreign policy; assessment the “journey” of the relations from year to year; the challenges of the relations. Threefold keys of progress cooperation under the Jokowi and Modi relations are maritime cooperation in the Indo-Pacific, multilateral engagement, and economic cooperation, while the shortcoming of the relations potentially derives from domestic politics policy, China factor, a reciprocal gap in the export tariffs. This article evaluates that despite the relations between the two countries successfully maintain closer ties through exploring a new area of collaboration namely maritime cooperation. This article recommends that the bilateral ties still require more implementation, exploring a new area of the partnership while at the same time managing potential threats within the bilateral ties for achieving maximum cooperation.